2008
DOI: 10.1186/1471-2458-8-348
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and HRQL: A cross-sectional survey among older Italian adults

Abstract: Background: The aim of this study is to investigate the association between social relationships and Health Related Quality of Life (HRQL) among the elderly in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 37 publications
9
40
1
6
Order By: Relevance
“…Morbidity was found to be the predictor that most nega vely impacted the physical domain, agreeing with the scien fi c literature, which evidenced the worst score in the physical component score among elderly with more than one chronic disease (37.59), compared with those who did not have diseases (48.72) (6) . The lowest QoL score associated with comorbidi es may have been related to poor access to health services, as well as possible limita ons imposed by the disease, which can nega vely infl uence the ability to work and to perform daily ac vi es measured in this domain (10) .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Morbidity was found to be the predictor that most nega vely impacted the physical domain, agreeing with the scien fi c literature, which evidenced the worst score in the physical component score among elderly with more than one chronic disease (37.59), compared with those who did not have diseases (48.72) (6) . The lowest QoL score associated with comorbidi es may have been related to poor access to health services, as well as possible limita ons imposed by the disease, which can nega vely infl uence the ability to work and to perform daily ac vi es measured in this domain (10) .…”
Section: Discussionsupporting
confidence: 73%
“…One study found that men have low self-esteem as they age and concluded that there is an infl uence of gender issues on health and QoL (5) . Another study with elderly in Italy showed that lower QoL scores in physical appearance were related to age, family income, being single and chronic diseases (6) .…”
Section: Introductionmentioning
confidence: 99%
“…As far as the correlation between social participation and QOL is concerned, there is evidence supporting the role of social factors in improving the QOL both in adults suffering from depressive disorders (Sung and Yeh 2007) and in older adults (de Belvis et al 2008;Berg et al 2006;Gabriel and Bowling 2004;Ho et al 2003). However, it must be stressed that there are important differences in the determinants of QOL between adults and older people, with health and functional ability having a much greater importance among the latter (Bowling 2008;Walker 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that income [4] [5] and life circumstances [6] [7] have positive relationships with HRQOL. Regarding social interaction, it has been reported that social network [8] and social support [7] [9] have positive relationships with HRQOL.…”
Section: Introductionmentioning
confidence: 99%